ANALISIS PREFERENSI KONSUMEN TERHADAP TANAMAN HIAS PADA TOKO BUNGA NURSERI KRISMALIN DI KOTA PALU - Hesti Nuryuliani; Saharia Kassa; Dafina Howara (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
Ornamental plants is one of horticultural plants that has agribusiness prospect in Indonesia.  The plants can be used for decorative purposes in room with its surrounding area and as symbols for feeling expression such as happiness and sadness. Along with increasing development              in ornamental plant business, the aim of the research was to analyze the preference of consumers  on deciding what ornamental plans they select at the nursery flower shop of Krismalin.                The research was located in Watu Moranggga street, Poboya, Palu. Thirty respondents selected incidentally were consumers of the Krismalin Nursery Flower Shop. The chi-square analysis indicated that the consumers’ were affected by attributes including flower life duration, flower size, price, container used, color and flower bud. The values of the attributes calculated using > were 35.87>7.81, 24.67>7.81, 23.06>7.81, 14.26>7.81, and 11.33> 7.81,and 9.73 > 7.81, respectively.  Types of plants did not affect the consumers’ preference as indicated by  (7.60<7.81). It is suggested to the shop owner that more attention should be paid to flower life duration, flower size, price, container used, color and flower bud. Key Words : Consumer preference and ornamental plants.